2007
DOI: 10.1242/dev.02862
|View full text |Cite
|
Sign up to set email alerts
|

Transitin, a nestin-like intermediate filament protein, mediates cortical localization and the lateral transport of Numb in mitotic avian neuroepithelial cells

Abstract: Neuroepithelium is an apicobasally polarized tissue that contains neural stem cells and gives rise to neurons and glial cells of the central nervous system. The cleavage orientation of neural stem cells is thought to be important for asymmetric segregation of fatedeterminants, such as Numb. Here, we show that an intermediate filament protein, transitin, colocalizes with Numb in the cell cortex of mitotic neuroepithelial cells, and that transitin anchors Numb via a physical interaction. Detailed immunohistologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Because Numb is a cytoplasmic adapter protein, it must be anchored to the cytoskeleton in order localize asymmetrically. Transitin, a type IV intermediate filament, has been shown in mitotic neuroepithelial cells to interact directly with Numb and provide an anchor site for Numb localization (Wakamatsu et al, 2007). We stained SHF explants for both Numb and Transitin, and found co-localization (Fig.…”
Section: Asymmetric Localization Of Numb Marks a Self-renewing Stem Cmentioning
confidence: 81%
See 1 more Smart Citation
“…Because Numb is a cytoplasmic adapter protein, it must be anchored to the cytoskeleton in order localize asymmetrically. Transitin, a type IV intermediate filament, has been shown in mitotic neuroepithelial cells to interact directly with Numb and provide an anchor site for Numb localization (Wakamatsu et al, 2007). We stained SHF explants for both Numb and Transitin, and found co-localization (Fig.…”
Section: Asymmetric Localization Of Numb Marks a Self-renewing Stem Cmentioning
confidence: 81%
“…Numb has also been shown to regulate neurogenesis in mouse embryos (Zhong et al, 2000;Zilian et al, 2001;Peterson et al, 2002;Li et al, 2003). Recent studies in chick have shown the requirement of the intermediate filament protein transitin for the proper intracellular localization of Numb in neural stem cells (Wakamatsu et al, 2007). has also been shown to be important in invertebrate cardiogenesis but little is known about Numb and vertebrate carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This protein is a developmentally regulated nestin-like intermediate filament and has been described as progenitor cell marker. In this way, transitin is present in neurogenic cells where it seems to play an important role in determining the intracellular localization of Numb during mitosis (Wakamatsu et al, 2007). The filament transitin has also been reported as an early glial marker for neural crest-derived glial cells and their precursors (Henion et al, 2000), opening the question about the origin of the different cells found in the diencephalic roof plate.…”
Section: Discussionmentioning
confidence: 97%
“…In mitotic avian neuroepithelial cells, transitin has been shown to interact physically with Numb, allowing its asymmetric distribution to one of the daughter cells (Wakamatsu et al, 2007). Thus, transitin could be considered as a factor promoting neural differentiation as Numb antagonizes Notch activation.…”
Section: Transitin and Myogenesis 3043mentioning
confidence: 99%
“…Immunoreactivity of this submembranous domain rapidly disappeared from points of cell-cell contacts when avian QM7 myoblasts were induced to fuse and differentiate into myotubes. It has recently been shown that transitin has important roles in determining the intracellular localization of the fate determinant Numb in avian mitotic neuroepithelial cells (Wakamatsu et al, 2007), suggesting it might indirectly regulate neurogenesis. These observations led us to investigate the potential role of transitin in an in vitro avian model of myogenesis, the QM7 cell line.…”
Section: Introductionmentioning
confidence: 99%